Genealogía de la 'corrigenda': mujeres encarceladas en Pamplona (siglos XVI-XIX) - Oliver Olmo, Pedro (Huarte de San Juan. Geografía e Historia, 1998)
In this article we make a reflexion about different penal treatment and discourses according to gender. With documents since XVIth century until XIXth century we analize two models of women imprisionment in Pamplona. This two different kinds of jail reclusion will come together in the end of XVIIIth century, and even more within the penal ideas of liberal State. The first one is the general one, that of the so called 'Cárceles Reales’ (Royal Prisions) Thought for both men and women with trials in course. The other one, that of the so called ‘casa-galera’, was specific for women punished because of sexual offences. Imprisioned woman was made object of correction, and this was part of an important process –decisive in Pamplona- that explains, along with some other factors, the rising of contemporary prision.
Keywords: Imprisioned women; punishment; sexual offences; correction